ANALISIS KOMPARASI PENDAPATAN PETANI PADI DENGAN MENGGUNAKAN PANEL SURYA DAN TANPA MENGGUNAKAN PANEL SURYA DI DESA CANDEN KABUPATEN BANTUL - Aulia, Alfin; Ratri, Wahyu Setya; Stefani, Eska (JURNAL ILMIAH AGRITAS, 2025)
The aim of this research is to analyze the comparison of income of rice farmers using solar panels and without solar panels. This research was conducted in Canden Village, Jetis District, Bantul Regency, Yogyakarta Special Region with a sample size of 36 respondents with a sample determination method using purposive sampling. The basic method used in this research is a quantitative descriptive method. R/C Ratio analysis method and independent t- test. The results of this research are the value of tcount < ttable (0.897 < 2.032), so H0 is rejected and H1 is accepted, meaning that there is a difference in income between rice farmers who use solar panels and rice farmers without solar panels. The average income of rice farming using solar panels is greater, namely Rp 38,143,494 /Ha compared to rice farming without using solar panels, namely IDR 23,694,105/Ha. R/C Ratio analysis of solar panel rice farming is 13.3 and rice farming without solar panels is 6.07, so it is said to be feasible. Therefore, the importance of using solar panel technology can increase rice farmers' income.